Add. Express you answer as a polynomial in standard form. (1 point)

(4x2−x+5)+(5x2+x+9)=
(
4
𝑥
2

𝑥
+
5
)
+
(
5
𝑥
2
+
𝑥
+
9
)
=

1 answer

To add the polynomials \( (4x^2 - x + 5) + (5x^2 + x + 9) \), we combine like terms.

  1. Combine the \( x^2 \) terms: \[ 4x^2 + 5x^2 = 9x^2 \]

  2. Combine the \( x \) terms: \[ -x + x = 0x \quad (\text{which simplifies to } 0) \]

  3. Combine the constant terms: \[ 5 + 9 = 14 \]

Now, putting it all together, we have: \[ 9x^2 + 0x + 14 \]

The polynomial in standard form is: \[ \boxed{9x^2 + 14} \]

Similar Questions
  1. Add. Express your answer as a polynomial in standard form:(5x3 +x^2−x) + (8x^2+3x + 1) (1 point)
    1. answers icon 1 answer
    1. answers icon 1 answer
  2. Multiply. Express your answer as a polynomial in standard form. (1 point)(3x−5)(9x+1)= ( 3 𝑥 − 5 ) ( 9 𝑥 + 1 ) =
    1. answers icon 1 answer
  3. Add. Express your answer as a polynomial in standard form. (1 point)(6x3−8x2+3x)+(10x2+9x+11)= ( 6 𝑥 3 − 8 𝑥 2 + 3
    1. answers icon 1 answer
more similar questions